Effect of Nb and Zr Alloying Additives on Structure and Properties of Ti-Ta-Nb-Zr Alloys for Medical Applications - G. Dercz; I. Matuła; K. Prusik; J. Zając; M. Szklarska; A. Kazek-Kęsik; W. Simka (Archives of Metallurgy and Materials)
This work investigated two titanium-based alloys with a constant tantalum content and variable contents of alloy additives – niobium and zirconium. The Ti-30Ta-10Zr-20Nb (wt.%) and Ti-30Ta-20Zr-10Nb (wt.%) alloys were obtained using a combination of powder metallurgy and arc melting methods. The influence of alloying additives on the structure and properties of the Ti-Ta-Nb-Zr system was studied using, among others: X-ray diffraction and scanning electron microscopy. The X-ray diffraction confirmed the single-β-phase structure of both alloys. In addition, the microscopic analysis revealed that a higher amount of zirconium favoured the formation of larger grains. However, the microhardness analysis indicated that the alloy with the higher niobium content had the higher microhardness. Importantly, the in vitro corrosion study revealed that the addition of niobium promoted the better corrosion resistance of the investigated alloy.